2007
DOI: 10.1094/ats-2007-1130-01-tt
|View full text |Cite
|
Sign up to set email alerts
|

Determining a Profile of Protocols and Standards used in the Visual Field Assessment of Turfgrasses: A Survey of National Turfgrass Evaluation Program-Sponsored University Scientists

Abstract: The National Turfgrass Evaluation Program (NTEP) is a not‐for‐profit organization that facilitates the assessment of experimental and commercial turfgrasses for the turfgrass seed and sod industries in cooperation with university turfgrass scientists. The objective of this survey was to identify and compare common protocol and standards used by NTEP‐sponsored university scientists to aid NTEP staff in writing a document entitled Protocol and Standards for the Visual Field Assessment of Turfgrasses. Twelve NTEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 0 publications
0
65
0
Order By: Relevance
“…Previous research has shown increased physiological function, as measured by canopy photochemical efficiency and leaf antioxidant and chlorophyll levels, for drought‐ or heat‐stressed creeping bentgrass due to repeated SWE application (Zhang and Ervin, 2004, 2008), but these measurements were not taken for the current study, nor was drought stress allowed. Visual quality ratings are a subjective assessment of a plot's uniformity, density, texture, and color (Krans and Morris, 2007). Given the canopy‐darkening effects of FeSO 4 , much of the quality differences noted in this study were due primarily to these color difference effects, with the most aesthetically pleasing color being provided by the medium FeSO 4 rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown increased physiological function, as measured by canopy photochemical efficiency and leaf antioxidant and chlorophyll levels, for drought‐ or heat‐stressed creeping bentgrass due to repeated SWE application (Zhang and Ervin, 2004, 2008), but these measurements were not taken for the current study, nor was drought stress allowed. Visual quality ratings are a subjective assessment of a plot's uniformity, density, texture, and color (Krans and Morris, 2007). Given the canopy‐darkening effects of FeSO 4 , much of the quality differences noted in this study were due primarily to these color difference effects, with the most aesthetically pleasing color being provided by the medium FeSO 4 rate.…”
Section: Discussionmentioning
confidence: 99%
“…Quality was rated 1 wk after each biweekly treatment during the growing season between March and November. Quality ratings were based on a 1‐to‐9 scale with 1 = dead, poor turf, 6 = minimally acceptable turf, and 9 = healthy, high‐quality turf (Krans and Morris, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Measured parameters included a visual rating of turf quality (TQ) on a scale of 1 to 9 based on color, density, and uniformity (Krans and Morris, 2007). Measured parameters included a visual rating of turf quality (TQ) on a scale of 1 to 9 based on color, density, and uniformity (Krans and Morris, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Physiological assessment was performed every 14 d after the initial spray each year. This included a visual rating of turf quality (TQ), which was measured on a 1 to 9 scale with 9 being the best for the qualities of color, density, and overall plant health (Krans and Morris, 2007). Membrane stability was estimated via electrolyte leakage (EL) using the protocol previously described by Blum and Ebercon (1981).…”
Section: Methodsmentioning
confidence: 99%